2020
DOI: 10.11648/j.abb.20200804.13
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Metformin in the Treatment of Non-alcoholic Fatty Liver Disease

Abstract: Backgroud: Nonalcoholic fatty liver disease has become the second largest source of chronic liver disease in the urban population. Metformin, a traditional drug, has good prospects for treating the disease in primary health care facilities. Objective: To summarize and grasp the status of metformin in adults, children with diabetes and non-diabetic NAFLD patients. Methods: We reviewed 31 relevant research literatures in PubMed database, and sorted out some preclinical and clinical research results. Results: Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…For Coptis chinensis Franch., which has the highest frequency of occurrence, pharmacological studies have shown that berberine is the main active ingredient, which has definite effects of reducing hepatocyte lipid accumulation, anti-inflammation, and anti-fibrosis (Li et al, 2021), lowering blood glucose and improving insulin resistance (Chen Y. et al, 2021), and providing typical multi-target and multi-system pharmacological effects on T2DM with NAFLD. Berberine can regulate hepatic metabolism by protecting the intestinal mucosal epithelial barrier, thereby regulating the microenvironment of the intestinal microbiota and changing microbiota-derived metabolites such as shortchain fatty acids and secondary bile acids (Betrapally et al, 2017;Sun et al, 2017;Tian et al, 2019).…”
Section: Frequency Distribution Analysis Of Chinese Herb Medicinesmentioning
confidence: 99%
“…For Coptis chinensis Franch., which has the highest frequency of occurrence, pharmacological studies have shown that berberine is the main active ingredient, which has definite effects of reducing hepatocyte lipid accumulation, anti-inflammation, and anti-fibrosis (Li et al, 2021), lowering blood glucose and improving insulin resistance (Chen Y. et al, 2021), and providing typical multi-target and multi-system pharmacological effects on T2DM with NAFLD. Berberine can regulate hepatic metabolism by protecting the intestinal mucosal epithelial barrier, thereby regulating the microenvironment of the intestinal microbiota and changing microbiota-derived metabolites such as shortchain fatty acids and secondary bile acids (Betrapally et al, 2017;Sun et al, 2017;Tian et al, 2019).…”
Section: Frequency Distribution Analysis Of Chinese Herb Medicinesmentioning
confidence: 99%